2022
DOI: 10.13005/ojc/380321
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of Phenyl Glycine-O-Carboxylic Acid: Preparation, Characterization, Electrochemical and Biological Properties

Abstract: Metal complexes are the effective therapeutic compound and it became more emerging field in the drug discovery and delivery. A novel ligand phenyl-glycine -o- carboxylic acid was synthesized and further complexed with the metal (II) chlorides. The synthesized metal complexes was interpreted by FT-IR spectroscopy, Ultra Violet- visible, 1H-NMR, molar conductance, magnetic susceptibility and thermogravimetric study. The electrochemical properties of the ligand and its complexes were inquired in DMF. Antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The resonance of the carboxylic protons (-COOH) were not detected in the spectra of the three complexes. In investigations [36][37] , Gemi oxacin, glycine and phenyl glycine-o-carboxylic acid Zn(II), Cu(II), Co(II), Sn(II), and Ce(III) a complex with ions was obtained and it was found that carboxyl and amino groups in the ligand molecules are involved in the study of the process of complexation with metal ions according to the 1H NMR spectrum. This once again con rms that the obtained data are consistent with previous studies.…”
Section: Nmr Analysismentioning
confidence: 99%
“…The resonance of the carboxylic protons (-COOH) were not detected in the spectra of the three complexes. In investigations [36][37] , Gemi oxacin, glycine and phenyl glycine-o-carboxylic acid Zn(II), Cu(II), Co(II), Sn(II), and Ce(III) a complex with ions was obtained and it was found that carboxyl and amino groups in the ligand molecules are involved in the study of the process of complexation with metal ions according to the 1H NMR spectrum. This once again con rms that the obtained data are consistent with previous studies.…”
Section: Nmr Analysismentioning
confidence: 99%